Level of Technology Acceptance and Factors That Influences the Use of MOOC at Public Universities - Haron, Hafiza; Hussin, Supyan; Yusof, Ahmad Rizal Mohd; Samad, Hafiza; Yusof, Hafidzan; Juanita, Anis (International Journal of Psychosocial Rehabilitation, 2020)
The aim of these studies is to investigate the acceptance level of MOOC and factors that might influence the use of MOOC at Public Universities. A quantitative technique which is a survey method was conducted at the selected public university where data were collected from 400 respondents. The analysis was then conducted by using Smart PLS software. Meanwhile, the Technology Acceptance Model was implemented as to obtain the findings of this study. The results showed that effort performance, social influence, facilitating condition, interest, motivation and course design are factors influencing MOOC usage among students at the particular university. The findings also show that the acceptance level of MOOC learning at this particular university was substantial due to some factors might influence the usage and encouragement of these technologies. The result also shows that there is an area of improvement in term of MOOC learning at these universities in order to make the technologies useful and can be beneficial for long term sight and lifelong learning especially in the context of distance education.